Non-volatile metabolomics analysis of heating withering method for processing white tea from Longjing 43 tea variety by UHPLC-Q-TOF/MS - Cui, Hongchun; Cheng, Zhiqiang; Shi, Daliang; Yin, Junfeng; Feng, Zhihui; Zhao, Yun; Zhang, Jianyong (Frontiers in Nutrition, 2026)
Withering is a crucial step in the production of white tea. However, the non-volatile metabolomic profile of white tea produced from the Longjing 43 cultivar using heated withering methods has not been fully elucidated. This study investigated the effect of a novel heated withering process on the taste quality and non-volatile metabolome of white tea. The application of heat significantly shortened the withering duration and enhanced the sensory quality of the tea. Specifically, white tea withered using hot air for 23 h, sunlight for 28 h, and fluorescent lamp for 31 h, all at 28 ± 1 °C, achieved higher taste sensory evaluation scores compared to traditional room-temperature withering at 20 ± 1 °C for 40 h. Non-targeted metabolomic analysis led to the identification of 1,372 metabolites across the different withering treatments. Relative to room-temperature withering, the heated withering processes—particularly hot air withering—resulted in higher concentrations of key taste-related compounds, including organic acids, amino acids, flavonoids, and catechins. Enrichment analysis of KEGG pathways indicated that the main metabolic pathways affected by heated withering were cysteine and methionine metabolism, glutathione metabolism, and isoquinoline alkaloid biosynthesis, with the most pronounced effects observed under hot air withering. In summary, hot air withering not only reduced the processing time but also improved the taste quality and markedly altered the profile of key metabolites in white tea.